Pengaruh Audit Tenure dan Auditor Switching pada Kualitas Auditor - Putri, Devi Lestari Pramitha; Habibi, Nursyaikhairul; Syahadatina, Rika; Alfian, Nurul; Rohmaniyah, Rohmaniyah; Gazali, Gazali (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The purpose of this research is to determine the influence of audit tenure and auditor switching on audit quality. This research uses quantitative methods. This research aims to analyze the causal relationship used to explain the influence of the independent variables, namely audit tenure and auditor switching on the dependent variable, namely audit quality. After determining the scope of the research, the researcher then determines the population to be tested. The population in this study are manufacturing companies listed on the IDX. Population is the entire group of people, events, or things and interests that researchers wish to investigate. The sampling technique used in determining the sample was purposive sampling. The results of this research are that audit tenure has no effect on audit quality and auditor switching has an effect on audit quality.